2009
DOI: 10.1177/0748233709106822
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of endothelium-dependent vasorelaxation in cadmium-hypertensive rats

Abstract: Abnormalities in the production and/or release of relaxing factors from the endothelium have been implicated in the development of hypertension in several animal models. Endothelium-dependent relaxation has been reported to be impaired in thoracic aorta in experimentally induced and genetically hypertensive rats. Present study has extented these observations to thoracic aorta of cadmium-hypertensive rats. The possible role of alterations in oxidant status was also studied. Hypertension was induced by the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 34 publications
4
11
1
Order By: Relevance
“…Our results are supported by experimental evidence showing roles of cadmium in oxidative stress, 47 endothelial dysfunction, 10,48,49 atherosclerosis formation, 10,50 hypertension 51,52 and kidney disease. 53 Cadmium-related vascular damage could be partly promoted by dysfunctional metallothionein production in endothelial cells.…”
Section: Discussionsupporting
confidence: 86%
“…Our results are supported by experimental evidence showing roles of cadmium in oxidative stress, 47 endothelial dysfunction, 10,48,49 atherosclerosis formation, 10,50 hypertension 51,52 and kidney disease. 53 Cadmium-related vascular damage could be partly promoted by dysfunctional metallothionein production in endothelial cells.…”
Section: Discussionsupporting
confidence: 86%
“…The associations between cadmium and PAD observed in SHS are consistent with experimental evidence supporting a variety of potential mechanisms for cadmium as an atherogenic factor, including promoting the formation of reactive oxygen species, 8 interfering with antioxidative stress responses, 8,53 promoting hypertension 54,55 and kidney disease, 56 and causing endothelial dysfunction and damage. [4][5][6]57 Cadmium could also act through epigenetic 58 and endocrine disruption [59][60][61] pathways.…”
Section: Discussionsupporting
confidence: 83%
“…More recently, other authors have demonstrated the influence of cadmium on kidney tissues resulting in the decrease of CYP4A11 and PPARs (peroxisome proliferator-activated receptors), with possible production of hypertension, sodium retention, glucose intolerance, dyslipidemia, and zinc depletion [54]. Other studies have shown that cadmium can cause a loss of molecules with vasodilating functions, such as nitric oxide [55], and it can also increase the effect of norepinephrine [56]. In conclusion, some other authors have demonstrated a cadmium-induced endothelial alteration, which would be mediated by an alteration in the functionality of the M1 acetylcholine receptors [57].…”
Section: Discussionmentioning
confidence: 99%